An exploratory study on counterfactual thinking in amyotrophic lateral sclerosis - Poletti, Barbara; Aiello, Edoardo Nicolò; Tagini, Sofia; Solca, Federica; Torre, Silvia; Colombo, Eleonora; Maranzano, Alessio; Bonetti, Ruggero; Schevegher, Francesco; Morelli, Claudia; Doretti, Alberto; Verde, Federico; et al. (Frontiers in Psychology, 2023)
Objectives This study aimed at exploring (1) the motor and non-motor correlates of counterfactual thinking (CFT) abilities in non-demented amyotrophic lateral sclerosis (ALS) patients and (2) the ability of CFT measures to discriminate these patients from healthy controls (HCs) and patients with and without cognitive impairment. Methods N = 110 ALS patients and N = 51 HCs were administered two CFT tasks, whose sum, resulting in a CFT Index (CFTI), was addressed as the outcome. Patients further underwent an in-depth cognitive, behavioral, and motor-functional evaluation. Correlational analyses were run to explore the correlates of the CFTI in patients. Logistic regressions were performed to test whether the CFTI could discriminate patients from HCs. Results The CFTI was selectively associated (p ≤ 0.005) with fluency and memory subscales of the Edinburgh Cognitive and Behavioral ALS Screen (ECAS), but not with other variables. CFTI scores discriminated patients from HCs (p < 0.001) with high accuracy (82%), but not patients with a normal vs. defective performance on the ECAS-Total. Conclusion CFT measures in non-demented ALS patients were associated with verbal fluency and memory functions, and they were also able to discriminate them from HCs.